1993
DOI: 10.1111/j.1399-302x.1993.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptostreptococcus micros has a uniquely high capacity to form hydrogen sulfide from glutathione

Abstract: There are high amounts of hydrogen sulfide in deep periodontal pockets. This volatile sulfur compound may be formed from L-cysteine, but only low levels of this amino acid can be expected to be present in periodontal pockets. Glutathione, L-gamma-glutamyl-L-cysteinylglycine, is in high concentration in most tissue cells, and this tripeptide may be more readily available as a source of hydrogen sulfide formation in the pockets. The ability of 37 different species of oral bacteria to utilize glutathione in hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 29 publications
0
55
1
Order By: Relevance
“…High levels of H 2 S (up to 2 mM) have been detected in infected periodontal pockets, while low levels have been detected in clinically healthy sites (22,34,36,42). In vitro, H 2 S has been shown to be cytotoxic for a variety of host cells, including gingival fibroblasts and epithelial cells (4, 10, 40, 48).Several reports have described H 2 S formation from metabolism of human serum proteins, cysteine, and glutathione by oral bacteria (6,37,38). Despite these observations, the metabolic pathways leading to H 2 S production from glutathione by oral bacteria have not been delineated.…”
mentioning
confidence: 86%
“…High levels of H 2 S (up to 2 mM) have been detected in infected periodontal pockets, while low levels have been detected in clinically healthy sites (22,34,36,42). In vitro, H 2 S has been shown to be cytotoxic for a variety of host cells, including gingival fibroblasts and epithelial cells (4, 10, 40, 48).Several reports have described H 2 S formation from metabolism of human serum proteins, cysteine, and glutathione by oral bacteria (6,37,38). Despite these observations, the metabolic pathways leading to H 2 S production from glutathione by oral bacteria have not been delineated.…”
mentioning
confidence: 86%
“…The lowered GSH levels found in PE do not necessarily imply its involvement in anti-oxidant activity, since its -SH may simply have been used by oral bacteria to form hydrogen sulfide (Carlsson et al, 1993;Tang-Larsen et al, 1995). However, whatever the reason for -SH reduction, the result is a lowered overall anti-oxidant potential of the periodontium.…”
Section: Dietary Intake Of Anti-oxidantsmentioning
confidence: 96%
“…In contrast, the thiol tripeptide is absent from gram-positive bacteria, with the exception of some members of the BacillusClostridium group (8,36,68). For that group however, it was shown that the GSH present in these cells was most often not the result of intrinsic biosynthesis but was acquired by import of a reducible form of GSH from the growth medium.…”
mentioning
confidence: 99%